Enhancing Poetry Writing Skills through the Implementation of the Acrostic Technique: A Case Study of Eighth-Grade Indonesian Students - Reifika Koumala Sari; Muhammad Safdar Bhatti (Yayasan Darussalam Bengkulu, 2024)
Poetry writing is a fundamental component of language learning that fosters creativity, expressive ability, and cultural appreciation, yet many students encounter difficulties in developing ideas, selecting appropriate diction, and structuring their poems coherently. This study aimed to investigate the effectiveness of the acrostic technique in improving poetry writing skills among eighth-grade students at SMP Negeri 11 Bengkulu Tengah. Employing a qualitative descriptive design, the research involved 27 students selected purposively, with data collected through classroom observations, semi-structured interviews, and documentation of student poetry. Data were analyzed through reduction, classification, and interpretation, with triangulation, peer debriefing, and member checking ensuring credibility. The results indicated significant improvement in students’ creativity, diction, and structural organization after the application of the acrostic technique, as reflected in richer vocabulary use, clearer thematic expression, and more coherent poetic forms. The discussion highlights that the acrostic method provides a structured yet flexible framework that stimulates student engagement and encourages originality, aligning well with the principles of the Merdeka Curriculum. The implication of this study is that the acrostic technique can serve as an innovative and practical pedagogical strategy to enhance poetry writing skills in secondary education, while also contributing to curriculum innovation and the promotion of literary creativity in language learning.